Uwarunkowania zależności dochodu rolniczego i przepływów pieniężnych w gospodarstwach rolniczych - Wasilewski, Mirosław (Conditioning of Correlation between an Agricultural Income and Cash Flows in Farms, 2006)
The paper presents the analysis of correlation between cash flows and an agricultural income amount in private farms. It is proved that farms of the highest income have the largest cash resources, which allow them to carry on investment activities. In these farms there is also the largest share of payments from taken credits as well as expenditure on fixed assets purchase. The largest balance of cash flows occurs in farms of the highest income, whereas in the group of the lowest income cash flows are usually negative and a level of cash resources is also too low. As a result, development possibilities of these farms can be limited. An ordinary activity (usually with the largest share in the group of farms with the highest income) dominates in the structure of cash payments in all farm groups and expenditure share on this activity is smaller than payments. In comparison to the other groups, larger share connected with payments from fixed assets sale and from private sources occurrs in the group of farms of the lowest income
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 660-672